(untitled) (Forum Penelitian Agro Ekonomi, 2021)
In line with climate change, it is predicted that risk and uncertainty of rice farming will be swelling up. To cope with its negative effects, conventional approach using one or combination of strategy of production, marketing, financial, and informal credit might not be appropriate. Development of agricultural insurance specifically rice farming, is highly considered. This article is aimed at a review of some strategic aspects for developing the agricultural insurance, especially related to the basic prerequisites for designing the scheme. To get better understanding, its perspective with empirical condition of rice farming in Indonesia is enriched with lesson learned from other countries that here previously developed the agricultural insurance.